Communications in the time of a pandemic: the readability of documents for public consumption. (18th January 2021) - Ferguson, Catherine; Merga, Margaret; Winn, Stephen
Abstract: Objective : Government communications in a crisis can influence public health outcomes. This research aimed to investigate if written communications of the most commonly sought sources of COVID‐19 information available on the internet have readability levels commensurate with those of the general public. Methods : Online documents from the World Health Organization (WHO), and the governments of Australia, the UK and the US were assessed for readability using an online instrument that calculated scores for the Flesch Reading Ease Score, the SMOG Index and the Readability Consensus Grade Level. Results : Similar to the previous research, most documents assessed had a readability standard that was at or above the recommended grade level, and as such inaccessible to substantial portions of the general public. A one‐way ANOVA with post hoc tests revealed significant differences among the data, with Australian documents significantly more difficult to read than those from the UK and US. Conclusions : Government departments need to consider their audience and monitor readability of the documents they produce to ensure that readers can understand them. Implications for public health : Health communications need to be written at a level appropriate for the targeted population in order to be fit for purpose.